Traffic Law Enforcement by Indonesian National Police Through a Restorative Justice Approach - Suprihanto, Eko (Proceedings of Police Academy, 2025)
Traffic law enforcement requires a renewal in the traffic law enforcement model. This is necessary considering that traffic is the lifeblood of society, and traffic can also be said to be a reflection of culture and the level of modernity of a nation. So that society can live, grow and develop, it requires productivity in its life which can be generated through activities supported by traffic. Traffic Law Enforcement aims to create order and regularity in community life, especially in traffic on the road. Traffic law enforcement is essentially for safety by raising awareness and even building civilization. The purpose of this research is to determine the renewal of the law enforcement model implemented, especially in the investigation of traffic accidents by the Police, through a restorative justice approach. The research method used is empirical legal research with the research specifications used being analytical descriptive. From the research results, it was found that the renewal of law enforcement for traffic crimes is based on 3 (three) foundations/aspects, namely philosophical, legal and sociological foundations. Furthermore, a new innovation is offered in the renewal of the law enforcement model for traffic crimes by the Indonesian National Police, namely electronic-based law enforcement in investigating traffic accident cases, through a restorative justice approach.